2013
DOI: 10.1103/physrevb.87.134106
|View full text |Cite
|
Sign up to set email alerts
|

Dislocation core radii near elastic stability limits

Abstract: Recent studies of transition metal alloys with compositions that place them near their limits of elastic stability (e.g. near the body-centered-cubic [BCC] to hexagonal-close-packed [HCP] transition) suggest interesting behavior for the dislocation cores. Specifically, the dislocation core size is predicted to diverge as the stability limit is approached. Here a simple analysis rooted in elasticity theory and the computation of ideal strength is used to analyze this divergence. This analysis indicates that dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Dominated by the behavior of chemical bonding, common slip, and nucleation of dislocations, [53][54][55] the ideal strength of solid materials sets the upper bound of the strength achievable by a real material under certain loading conditions. Investigations of the ideal strength are fundamental to understand the behavior of fracture, failure, [56][57][58] and creep [59,60] for advanced materials as well as to determine the gap between the real strength of materials and their ideal strength. [61] Ab initio computational [110] tensile and {111} 11 2 shear tests were implemented in stoichiometric Ni 3 Al, and the ideal strength and corresponding strains calculated according to Eqs.…”
Section: Resultsmentioning
confidence: 99%
“…Dominated by the behavior of chemical bonding, common slip, and nucleation of dislocations, [53][54][55] the ideal strength of solid materials sets the upper bound of the strength achievable by a real material under certain loading conditions. Investigations of the ideal strength are fundamental to understand the behavior of fracture, failure, [56][57][58] and creep [59,60] for advanced materials as well as to determine the gap between the real strength of materials and their ideal strength. [61] Ab initio computational [110] tensile and {111} 11 2 shear tests were implemented in stoichiometric Ni 3 Al, and the ideal strength and corresponding strains calculated according to Eqs.…”
Section: Resultsmentioning
confidence: 99%
“…[2] For example, in some special materials, the width of the dislocation core is related to the size of its ideal shear strength, and the local stress of cleavage crack nucleation must be greater than its ideal uniaxial tensile strength. [3][4][5] The ideal strength sets an upper bound for the strength of a real material. The simplest approach to determine the ideal strength is calculating the stress-strain curve of a system in the deformation process, and takes the first maximum or minimum point of the stress-strain curves as the ideal strength of materials.…”
Section: Introductionmentioning
confidence: 99%
“…By defining the dislocation core as the region for which the stress predicted by linear elasticity theory is greater than the ideal strength, an approximation for the region in which linear elasticity theory is no longer valid is obtained. 6,7 Since symmetry often links the ideal strength to the elastic constants, this definition allows for the dislocation core radius to be written in terms of the elastic constants. In the case of a BCC metal the dislocation core radius can be expressed as…”
Section: Theorymentioning
confidence: 99%
“…Subsequent work on Gum Metal suggested that a more general connection can be made between the properties of Gum Metal and the proximity of a material to an elastic instability. [5][6][7][8] Gum Metals exist near the composition at which the body-centered cubic (BCC) phase becomes elastically unstable and transforms into the hexagonal close-packed (HCP) phase. The proximity to this lattice instability is apparent in the elastic constants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation